2017
DOI: 10.3390/fermentation3030029
|View full text |Cite
|
Sign up to set email alerts
|

Fortification and Elevated Alcohol Concentration Affect the Concentration of Rotundone and Volatiles in Vitis vinifera cv. Shiraz Wine

Abstract: Abstract:Rotundone is a key aromatic compound for cool-climate Shiraz. This compound is produced in the skin of grape berries and extracted into wine during fermentation. This project investigated the influence of fermentation techniques on the concentration of rotundone in the resultant wine. Wine was fortified with ethanol and sucrose on the 1st and 5th days of fermentation and rotundone, volatile aroma compounds and colour were assessed in the resultant wine. The relationship between the concentration of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(64 reference statements)
0
2
1
Order By: Relevance
“…The absence of contribution to the models from sugar concentration at harvest is somewhat unexpected. Although recent studies have shown that an increased alcohol content of wine improves rotundone extraction rate from grapes into wine (Zhang et al, 2017), our data suggest that ethanol concentration in the resulting wines had no effect on rotundone concentration. This may be explained by the relatively small amplitude of difference between the lowest and highest sugar concentrations (20.1°Brix and 22.8°Brix, respectively) recorded between blocks for the 2 years of the study.…”
Section: Figure 2 Predicted Versus Observed Rotundone Concentrationcontrasting
confidence: 87%
“…The absence of contribution to the models from sugar concentration at harvest is somewhat unexpected. Although recent studies have shown that an increased alcohol content of wine improves rotundone extraction rate from grapes into wine (Zhang et al, 2017), our data suggest that ethanol concentration in the resulting wines had no effect on rotundone concentration. This may be explained by the relatively small amplitude of difference between the lowest and highest sugar concentrations (20.1°Brix and 22.8°Brix, respectively) recorded between blocks for the 2 years of the study.…”
Section: Figure 2 Predicted Versus Observed Rotundone Concentrationcontrasting
confidence: 87%
“…Actually, as other secondary metabolites, rotundone synthesis must be an energy demanding process that requires carbohydrates. As rotundone is hydrophobic and was measured indirectly in wine, we can also suppose that the difference in ethanol content between the two vintages might have impacted its extraction from the berry pericarp, which is enhanced by fortification and elevated alcohol concentration (Zhang et al, 2017). IBMP concentrations were below detection level in wines from 2015 which could be a result of the heat wave experienced between berry set and bunch closure in July.…”
Section: Controlmentioning
confidence: 99%
“…This information should be used for follow-up studies as a starting point for proper experimental design. This relatively low number of publications on cold-hardy wine varieties is significant compared with active research in Vinifera [52,53,54,55,56,57,58,59,60,61,62].…”
Section: Discussionmentioning
confidence: 99%